The Influence of Transformational Leadership Style and Organizational Culture on Employee Performance at Dwi Warna Vocational School Sukabumi - Rahmat Hidayat; Deri Firmasyah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research is to determine and analyze the influence of transformational leadership style and organizational culture on employee performance, both partially and simultaneously. This research was carried out at Dwi Warna Sukabumi Vocational School with a total of 38 respondents, consisting of 31 teachers, 2 administrative staff (TU), 3 toolmen and 2 security staff. This type of research is a type of quantitative research. In this research, data was obtained from research instruments using a questionnaire and then analyzed using several tests including validity test, reliability test, classical assumption test, multiple regression analysis, coefficient of determination, and hypothesis testing via t test and f test. Based on the hypothesis test, it is known that there is a positive and significant influence between the variable Transformational Leadership Style (X1) on Employee Performance (Y) with a t-count > t-table value of 6.174 > 1.690 and a significance value of 0.000 < 0.05. Meanwhile, the Organizational Culture variable (X2) on Employee Performance (Y) has a t-count > t-table value of 5.146 > 1.690 and a significance value of 0.000 < 0.05. Simultaneously, it is known that the variables Transformational Leadership Style (X1) and Organizational Culture (X2) simultaneously have a positive and significant effect on Employee Performance (Y) with an f-count > f-table value of 83.542 > 1.690 and an Adjusted R Square value of 0.817 > 0.5 (categorized as well influenced), then the contribution of the Independent Variable to the Dependent Variable simultaneously is 81.7% and the remainder is influenced by other factors not examined in this research